Facile Synthesis of Atomic Fe‐N‐C Materials and Dual Roles Investigation of Fe‐N4 Sites in Fenton‐Like Reactions - Wang, Jun; Li, Bin; Li, Yang; Fan, Xiaobin; Zhang, Fengbao; Zhang, Guoliang; Peng, Wenchao (Advanced science, 2021)
Fenton‐like reactions with persulfates as the oxidants have attracted increasing attentions for the remediation of emerging antibiotic pollutions. However, developing effective activators with outstanding activities and long‐term stabilities remains a great challenge in these reactions. Herein, a novel activator is successfully synthesized with single iron atoms anchored on porous N‐doped carbon (Fe‐N‐PC) by a facile chemical vapor deposition (CVD) method. The single Fe atoms are coordinated with four N atoms according to the XANES, and the Fe‐N4‐PC shows enhanced activity for the activation of peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX). The experiments and density functional theory (DFT) calculations reveal that the introduction of single Fe atoms will regulate the main active sites from graphite N into Fe‐N4, thus could enhance the stability and tune the PMS activation pathway from non‐radical into radical dominated process. In addition, the N atoms connected with single Fe atoms in the Fe‐N4‐C structure can be used to enhance the adsorption of organic molecules on these materials. Therefore, the Fe‐N4‐C here has dual roles for antibiotics adsorption and PMS activation. The CVD synthesized Fe‐N4‐C shows enhanced performance in persulfates based Fenton‐like reactions, thus has great potential in the environmental remediation field. A novel SACs (Fe‐N‐PC) is successfully synthesized by a facile chemical vapor deposition (CVD) method. The introduction of single iron atoms enhances the stability and tune the PMS activation pathway from non‐radical into radical process. In addition, the N atoms connected with iron atoms in Fe‐N4‐C structure are proved to be able to enhance the adsorption of organic molecules.